Analysis of Neuroscience-Based Learning on Critical Thinking Skills of Elementary School Students - Deo Arief Oktavianto; Aynin Mashfufah; Ade Eka Anggraini; Radeni Sukma Indra Dewi; Ratna Ekawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Learning should provide educational experiences that stimulate brain function as part of a meaningful learning method. However, currently, the problem is that most teachers only use conventional learning. This study aims to analyze neuroscience-based learning on the learning responses of elementary school students. Neuroscience-based learning integrates knowledge about how the brain works in learning with teaching methods that can stimulate students' cognition, emotions, and motivation. This study used a qualitative research design method. Data were collected through interviews with three high school teachers at the level and observations during learning with 53 students, as well as observations of student motivation and engagement during the learning process. The results of the study indicate that the implementation of neuroscience-based learning is good, as evidenced by the active responses given by students when teachers provide questions or stimuli. However, it still requires evaluation and improvement to help maximize the improvement of critical thinking skills. Teachers apply creative and innovative strategies in neuroscience-based learning in the classroom by using video aids and concrete media to help students more easily remember what they know, as well as fostering student sensitivity in learning to activate brain function. Student learning success is only assessed through evaluation of outcomes, namely by using descriptive questions, not evaluation of the processes that occur during learning. The role of the principal and teachers is a crucial factor in the success of learning, this can be proven by paying more attention to learning methods, the use of learning media with the hope of always synergizing in realizing new neuroscience-based learning methods and strategies in schools to support maximum learning outcomes.